Early cenozoic vegetation in patagonia: New insights from organically preserved plant fossils (ligorio márquez formation, Argentina) - Carpenter, Raymond J. (2018)
Premise of research. Cenozoic macrofloras from South America are fundamental for understanding extant Southern Hemisphere biotas. The Paleogene Ligorio Márquez Formation (LMF) straddles the Chile-Argentina border; leaf fossils from its Chilean outcrops were previously assigned to >50 morphotypes and interpreted as primarily representative of tropical-subtropical lineages, with dominance by diverse Lauraceae of extant Neotropical affinities. Here, we present new collections of Argentine LMF mudstones that are thus far unique in the Patagonian region in containing organically preserved plant fossils, including leaves with cuticular preservation. Methodology. Leaf fossils were exposed by splitting blocks of mudstone or collected by flotation from disaggregated samples. Smaller fossils, including reproductive parts, conifer needles, and isolated cuticles, were recovered from sieved slurry. Fossils were examined under light microscopy, epifluorescence, and SEM. Pivotal results. Twenty taxa were recognized from cuticle-bearing leaf fossils or dispersed cuticles. The most abundant leaf species is a morphologically variable form that is like Lauraceae in architecture but with clearly nonlauraceous cuticular details. Four-parted flower fossils are attributable to the same species, and its eudicot affinities are indicated by adherent triaperturate pollen. Lauraceae were present but much less diverse than reported from the LMF in Chile and arguably with Gondwanan (not Neotropical) affinities. Other taxa include the conifers Dacrycarpus chilensis and Coronelia molinae and possibly Cunoniaceae and a new Ginkgoites. A wet mesotherm paleoclimate is inferred. Conclusions. The new fossils complement and improve our understanding of the LMF and contribute to a greater understanding of high southern latitudes at a time when overland dispersal was possible between South America and Australasia. The fossils provide further evidence for warm and humid climates in Patagonia during the early Paleogene and for a strongly Gondwanic flora, with little conclusive evidence of taxa belonging to Neotropical and megatherm lineages.